2020
DOI: 10.1111/and.13763
|View full text |Cite
|
Sign up to set email alerts
|

The possible association between serum interleukin 8 and acute urinary retention in Chinese patients with benign prostatic hyperplasia

Abstract: Acute urinary retention (AUR) is one of the progressive manifestations of benign prostatic hyperplasia (BPH). This cross‐sectional study was conducted to analyse the possible association between serum interleukin 8 (sIL‐8) and AUR in BPH patients to provide evidence of sIL‐8 as a potential biomarker for the prediction of AUR. The relationship between sIL‐8 levels and AUR was evaluated by logistic regressions in 245 ageing Chinese men with BPH. The discriminant validity of sIL‐8 and the optimal cut‐off value we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In clinical practice, postoperative urinary retention is often prevented and treated by intermittent clamping of urinary catheters, functional exercises for the pelvic floor, bladder irrigation, and potassium permanganate sitz baths [20][21][22]; Chinese medicine classifies urinary retention under the category of "retention of urine." The pathogenesis of the disease is mainly due to trauma, which causes damage to the ramifications of the stroke and veins, blockage of the tendons and veins, failure to consolidate the essence and blood, resulting in deficiency of qi and blood, unfavorable qi- transformation of the kidneys and bladder, and failure to open and close the bladder, resulting in blockage of urination [23][24][25]. The main lesion is in the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, postoperative urinary retention is often prevented and treated by intermittent clamping of urinary catheters, functional exercises for the pelvic floor, bladder irrigation, and potassium permanganate sitz baths [20][21][22]; Chinese medicine classifies urinary retention under the category of "retention of urine." The pathogenesis of the disease is mainly due to trauma, which causes damage to the ramifications of the stroke and veins, blockage of the tendons and veins, failure to consolidate the essence and blood, resulting in deficiency of qi and blood, unfavorable qi- transformation of the kidneys and bladder, and failure to open and close the bladder, resulting in blockage of urination [23][24][25]. The main lesion is in the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some prostatic inflammation-related inflammatory mediators may contribute to the progression of BPH, especially resulting in the occurrence of AUR. The positive association between the serum interleukin 8 concentration and the risk of AUR in elderly men suffered BPH has been revealed by our previous study (24). Moreover, high levels of sIL-6 have been confirmed as correlating with an increased risk of BPH in a dose-dependent pattern (37).…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, certain inflammatory mediators may help to predict the possible risk of AUR in BPH patients. Moreover, our previous study has found that the serum level of interleukin (IL)-8 is positively associated with the probability of suffering AUR in elderly men with BPH (24).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers used univariate and multivariate logistic regression analyses to conduct a cross-sectional study of sIL-6 and sIL-8 in 256 and 245 BPH patients and found that the levels of sIL-6 and sIL-8 in the AUR group were positively correlated with AUR. The odds ratios were [OR =1.365, 95% confidence interval (CI): 1.174–1.586, P<0.001] and [OR = 1.024, 95% CI: 1.009– 1.040, p = 0.002] ( 44 , 45 ). The significance of these studies is to expose potential treatment sites for BPH patients with immunological inflammation, to screen high-risk groups of AUR through blood tests, to provide patients with early intervention opportunities, to further improve the prognosis and to improve the quality of life of patients.…”
Section: The Role Of Inflammation In Bphmentioning
confidence: 99%